Phase transitions of a mixed spin ferrimagnet in high temperatures - A. Obaid, Intesar; Shakir D. Al-Saeedi; Hadey K. Mohamad (University of Thi-Qar Journal of Science, 2023)
In this research paper molecular mean field theory (MMFT) has been investigated based on Gibbs-Bogoliubov free energy function of a ferromagnetic mixed spin-3 and spin-5/2 Blume-Capel model with different magnetic crystal fields. The free energy of the proposed ferrimagnet has been evaluated depending on the trial Hamiltonian operator. Minimizing the free energy, one may induce characteristic features of the longitudinal magnetizations, phase transitions and spin compensation temperatures, in the ranges of low temperatures, respectively. In particular, we study the effect of crystal field domains on the critical phenomena for the proposed model. The sublattice magnetization dependence of freerenergy function has been discussed as well. Our results predict the existence of multiple spin compensation sites in the disordered Blume-Capel Ising system for a simple cubic lattice.